"Food Comes First": The Development of Colonial Nutritional Policy in Ghana, 1900–1950. Issue 2 (3rd July 2018) - Robins, Jonathan E.
ABSTRACT: This article examines the origins of colonial-era nutrition policy in Ghana (the colonial Gold Coast). It shows how imperial ideas about food and nutrition evolved in response to changing conditions in Ghana, as well as in response to new ideas originating outside Africa. British officials initially assumed food was abundant, identifying a growing taste for imports among urban elites as a key problem. By the early 1920s, new personnel with new priorities began to investigate local foodways, laying the groundwork for policies emphasizing nutrition, food production, and domestic education that were often continued into the post-colonial period.